SEASONAL VARIATION OF ACUTE OTITIS EXTERNA PRESENTING TO AYUB TEACHING HOSPITAL, ABBOTTABAD - Shah, Mohammad Imran; Sajid, Tahira; Ali, Syed Maisam; Ibrahim, Muhammad; Zaman, Akhtar; Shinwari, Wajih-ud-din (Journal of Ayub Medical College Abbottabad, 2019)
Background: Otitis Externa is a common inflammatory condition of external ear. It is more common in patients having predisposing conditions like trauma, swimming, patients using hearing aids, certain skin pathologies and immunocompromised patients. Increased humidity in rainy season increases the predisposition to otitis externa. Method: This descriptive study was carried over the duration of one year in ENT department of Ayub Teaching Hospital, Abbottabad. Patients of all ages and both genders suffering from acute otitis externa were included in the study after taking informed consent. All the information’s were recorded in predesigned proforma and then finally evaluated by using SPSS program. Results: The mean age of the patients presenting to us was 39.84±14.48 years (Range 1-78 Years) more commonly in male patients (54.14%). The disease was most commonly seen in rainy season, presenting unilaterally and affecting young adults of age ranging from 31-40 years. Conclusion: Prevalence of otitis externa is more common in humid climate. Precautionary measures should be taken in rainy and humid condition such as avoidance of self cleaning the ear. Keywords: Otitis Externa; Humidity; cleaning the ear